Implementation of agile approach in developing adverse drug reaction monitoring system at pharmacy - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
Healthcare systems are increasingly adopting Agile methodologies to address the complexities of software development in dynamic environments. This study investigates the application of Agile methodology in developing an adverse drug reaction monitoring system within a pharmacy context. The research focuses on identifying user requirements, employing iterative Agile practices, and evaluating functional outcomes. Through an analysis of user needs and preferences, wireframing, and iterative development cycles, the study demonstrates the effectiveness of Agile in meeting evolving demands and ensuring user satisfaction. Results indicate that Agile methodology facilitates flexible and responsive development, enabling continuous improvement and adaptation to changing requirements. The collaborative nature of Agile fosters stakeholder engagement and communication, enhancing the relevance and usability of the monitoring system. This research contributes to the growing body of literature on Agile methodology in healthcare software development, providing insights into its application, benefits, and implications for pharmacy settings.